A framework for teaching software engineering introductory courses. (1st January 2011) - Alsmadi, Izzat; Hanandeh, Feras
Teaching in continuously evolving fields such as software engineering is challenging due to the need for continuous evaluation and evolution in the course material and subjects. As a result, students may have problems connecting the different course subjects and concepts together. In this research, a software engineering high level conceptual knowledge is presented. The goal is to decompose knowledge terms in software engineering and projects based on several perspectives. This can also help making a distinction between the different activities that occur in each area such as activities related to management, planning, progress evaluation, etc. We also presented a plan for teaching software engineering courses with industrial orientation. Bridging the gap between academia and the industry can be a win-win solution for both sides. One year practical training is proposed in the software engineering degree to give students' the skills to communicate with the IT companies and be exposed to actual projects and real time scenarios.